Triplets under the tree - Senate, Melissa (Harlequin special edition., 2023)
"Rancher Hutch Dawson is desperate for a nanny for his six-month-old triplets. Then, Savannah Walsh comes knocking--with a proposal! His longtime rival, Savannah has secretly always loved Hutch, and offers to be his nanny in exchange for the chance to experience life with a family. It's a Christmas miracle Hutch can't refuse. Juggling diapers, feedings and story time, Hutch and Savannah prove they're better partners than rivals. And maybe, the five of them can be a forever family for Christmas..."--